Antisocial behavior reduces the association between subdimensions of ADHD symptoms and alcohol use in a large population‐based sample of adolescents. Issue 5 (11th June 2015) - Lövenhag, Sara; Larm, Peter; Åslund, Cecilia; Nilsson, Kent W.
Abstract : The aim of this study was to investigate possible effects of antisocial behavior on reducing the association between subdimensions of ADHD symptoms (inattention, hyperactivity and impulsivity) and alcohol use. Boys and girls were analyzed separately using a population‐based Swedish adolescent sample. A randomly selected cross‐sectional survey was performed in secondary and upper secondary schools in Västmanland County during 2010. Participants were a population of 2, 439 15–16 year‐olds and 1, 425 17–18 year‐olds (1, 947 girls and 1, 917 boys). Psychosocial adversity, antisocial behaviors, symptoms of ADHD and alcohol use were assessed by questionnaires. Except for girls' inattention, subdimensions of ADHD symptoms were not associated with alcohol use when variance due to antisocial behavior was accounted for. Among boys, instead of an indirect effect of antisocial behavior on the association between impulsivity and alcohol use, a moderating effect was found. Among girls, the inattention component of ADHD was independently associated with alcohol use even when adjusted for antisocial behavior. The reduced associations between symptoms of hyperactivity, impulsivity, and alcohol use for boys and girls after adjusting for antisocial behavior suggest a considerable overlap between hyperactivity, impulsivity, and antisocial behavior. The direct pathway between inattention and alcohol use among girls suggests that girls with inattention symptoms are at risk of alcohol use regardless of antisocial behavior. Special attention should be given to these girls. Accounting for antisocial behavior reduced the relation between subdimensions of ADHD symptoms and alcohol use, and antisocial behaviors should therefore be screened for when symptoms of ADHD are present.